Oxidative Stress and Covalent Modification of Protein with Bioactive Aldehydes - Grimsrud, Paul A.; Xie, Hongwei; Griffin, Timothy J.; Bernlohr, David A. (The Journal of biological chemistry, 2008)
The term “oxidative stress” links the production of reactive oxygen species to a variety of metabolic outcomes, including insulin resistance, immune dysfunction, and inflammation. Antioxidant defense systems down-regulated due to disease and/or aging result in oxidatively modified DNA, carbohydrates, proteins, and lipids. Increased production of hydroxyl radical leads to the formation of lipid hydroperoxides that produce a family of α,β-unsaturated aldehydes. Such reactive aldehydes are subject to Michael addition reactions with the side chains of lysine, histidine, and cysteine residues, referred to as “protein carbonylation.” Although not widely appreciated, reactive lipids can accumulate to high levels in cells, resulting in extensive protein modification leading to either loss or gain of function. The use of mass spectrometric methods to identify the site and extent of protein carbonylation on a proteome-wide scale has expanded our view of how oxidative stress can regulate cellular processes.